Bacteria induce release of platelet-activating factor (PAF) from polymorphonuclear neutrophil granulocytes: possible role for PAF in pathogenesis of experimentally induced bacterial pneumonia. - Makristathis, A (1993)
The role of platelet-activating factor (PAF) as mediator of the endotoxin shock and endotoxin-dependent tissue injury has been examined. The ability of opsonized bacteria to stimulate the release of PAF from human polymorphonuclear neutrophil granulocytes was evaluated by measuring both the activity and the amount of the mediator released in the supernatant of the cell-bacteria reaction in vitro. There was no significant difference between gram-positive and gram-negative bacteria in the ability to release PAF from neutrophils. However, preincubation of the cells with the specific PAF receptor antagonist WEB 2170 decreased release of PAF from the cells. Furthermore, a possible protective effect of the PAF antagonist was examined during experimentally induced pneumonia with Klebsiella pneumoniae in NMRI mice. Oral treatment of mice with WEB 2170, followed by infection with the microorganisms, resulted in a considerable increase in the animals' survival (53 to 73%) compared with the control group (40%); this increase corresponded with a decrease in the CFU per gram of lung tissue. These findings indicate an important role of PAF in the pathogenesis of pneumonia in mice.